2006
DOI: 10.1177/089686080602600510
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Extracellular Volume Expansion are Related to Sodium and Water Removal in Patients on Peritoneal Dialysis

Abstract: Background Inflammation is an important risk for mortality in dialysis patients. Extracellular fluid volume (ECFv) expansion, a condition commonly seen in peritoneal dialysis (PD) patients, may be associated with inflammation. However, published support for this relationship is scarce. Objectives To quantify the proportion of patients on PD with inflammation and to analyze the role of ECFv expansion and the factors related to these conditions. Design A prospective, multicenter cross-sectional study in six hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
3
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 40 publications
5
43
3
2
Order By: Relevance
“…One of the major shortcomings of short thrice weekly dialysis is inadequate removal of volume and consequent difficulty in controlling blood pressure (63)(64)(65). Volume overload is known to be associated with increased inflammatory markers and hypoalbuminemia (47,48).…”
Section: Hemodynamic Stability and Volume Controlmentioning
confidence: 99%
“…One of the major shortcomings of short thrice weekly dialysis is inadequate removal of volume and consequent difficulty in controlling blood pressure (63)(64)(65). Volume overload is known to be associated with increased inflammatory markers and hypoalbuminemia (47,48).…”
Section: Hemodynamic Stability and Volume Controlmentioning
confidence: 99%
“…31 This may be a contributing factor to elevated inflammatory markers in HD patients. 32,33 This notion is corroborated in observations made in patients with CHF showing that therapy with loop diuretics results in lower levels of circulating endotoxins with edema reduction. 34 Bowel wall edema may also result in protein losing enteropathy and fat malabsorption, as it also has been shown in patients with CHF.…”
Section: Consequences Of Chronic Overhydrationmentioning
confidence: 62%
“…39,40 Chronic inflammation, often presenting as the malnutrition inflammation complex syndrome, is also very common in prevalent dialysis populations with as many as 30% to 60% dialysis patients affected in the United States and Europe. 12 Numerous studies on congestive heart failure, [41][42][43] predialysis chronic kidney disease, 17 and peritoneal dialysis populations [19][20][21][22] have demonstrated that fluid overload and markers of chronic inflammation strongly correlate. Our present paper is one of the firsts to demonstrate similar relationships in a population on stable maintenance hemodiafiltration.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recently, two important phenomena were added as factors intertwined with inadequate volume control and poor outcomes: chronic inflammation [11][12][13] frequently manifesting in malnutrition-inflammation complex syndrome 14 and myocardial stunning often seen in the setting of hemodynamic instability during the hemodialysis procedure. 13,15,16 The majority of studies exploring these relationships were performed in either predialysis 17,18 or peritoneal dialysis patients [19][20][21][22] or hemodialysis patients who were recently hospitalized or discharged and data on maintenance hemodiafiltration is scarce. 23,24 Here, studied the relationship between fluid overload, inflammatory markers, and serum albumin in stable end-stage renal disease (ESRD) patients on maintenance hemodiafiltration, who received bioimpedance spectroscopy analysis as part of their routine care.…”
Section: Introductionmentioning
confidence: 99%